The management of allergic rhinitis by pharmacists in public services: a proposed PhaRmacISt-led Education Model (AR-PRISE) - Chii-Chii Chew; Chee-Tao Chang; Xin-Jie Lim; Wai-Yin Yong; Doris George; Pathma Letchumanan; Philip Rajan; Chee Ping Chong (Taylor & Francis Group, 2022)
Allergic rhinitis has been identified as a major respiratory disease that places a significant burden on patients and the healthcare system. Nevertheless, the management of allergic rhinitis is challenging for both patients and practitioners. Pharmacists have been recognised as strategic in providing advice for allergic avoidance, disease information, and pharmacological care for allergic rhinitis management. This role has been underutilised in the public health service sector in Malaysia due to variation in practice, regulation, and health system structures when compared to the international guidelines. This article proposed a PhaRmacISt-led Education Model (AR-PRISE) that includes explicit patient education materials and an algorithm for structured counselling by pharmacists in the management of patients with allergic rhinitis.